How to Manage Migratory Pests and Potential Food Crises: Locusts Plagues in the 2020's - Lecoq, Michel; Cease, Arianne (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Locusts are a threat to agriculture and livelihoods in many countries globally. The economic, social, and environmental consequences of these highly migratory pests are so substantial that they are treated as a national priority by many countries; several international commissions have been established to unite efforts. This Special Issue aims to shed light on some overarching questions: what have we learned from historical outbreaks; how serious is the threat; what research is ongoing and is needed to better manage these insects; how should the world respond to plagues today, especially in the context of climate change; are recommended preventive strategies really effective and what are the constraints to their application; and is there a possibility to make better use of biological alternatives to chemical pesticides?